The Effect of Storage Longtime on Cyanide Production in Postmortem Stored Tissues - Saeeid Gholamzadeh; Maryam Akhghari; Mohammad Zarenezhad; Jaber Gharedaghi; Mahmoud Montazeri; Alireza Doroodchi; Bahare Kazemi (Fasa University of Medical Sciences, 2016)
Background & Objective: Acute cyanide poisoning happens intentionally as suicide attempt or in accidental use. Interpretation of cyanide analysis results in postmortem samples is important in forensic medicine. Material & Methods: In this case-control study, the liver and the lung of 100 autopsy cases were collected during six months in Shiraz Forensic Medicine Department. Samples were divided into three parts and were examined as follow: one part of the liver and the lung was analyzed qualitatively to detect cyanide with Prussian blue test at first day of admission, the second and the third parts of the samples were stored at 0-4°C for one and two months, respectively. Then, liver and lung samples were analyzed to measure the amount of cyanide. Results: Cyanide was detected in only six cases in all three parts of the liver samples. Screening results for cyanide were negative for the remaining 94 liver samples. Conclusion: Endogenous cyanide production was not detected in liver and lung samples in this study. Therefore, cyanide detection was not affected by the time of the storage of the samples. The cyanide level changes in mentioned tissues were not significant. More importantly, our results would be more advantageous if we studied quantitatively on more samples to pave the way for future studies.